Generation of Computational 3D Models of Human Bones Based on STL Data and CAD Software Packages - Dan Leordean; Cristian Vilău; Mircea Cristian Dudescu (Applied Sciences, 2021)
This paper presents three methods of converting complex 3D models of STL type into solid models. For converting the STL models, specific approximation functions from CATIA and Creo Parametric software were used as well as 3D solid modeling methods that used sketches drawn for sections of the specific analyzed model. This conversion is required to get a solid 3D model that can be used for finite element analysis and to be processed using Boolean functions in specific CAD programs. This paper also presents a study of the effectiveness of FEA in respect to the time required for the analysis of each converted model. The analyzed STL files contain data obtained by computer tomography and are the 3D models of the human orthopedic system: the left zygomatic bone and upper part of the right femur. The presented conversion methods can be used by design engineers both in medical applications (where the complexity of forms is well known) for the design of implants and for industrial applications for reverse engineering.